2017
DOI: 10.1371/journal.pone.0172713
|View full text |Cite
|
Sign up to set email alerts
|

Low level of extra-pair paternity between nearest neighbors results from female preference for high-quality males in the yellow-rumped flycatcher (Ficedula zanthopygia)

Abstract: Extra-pair copulation is considered to be a means by which females can modify their initial mate choice, and females might obtain indirect benefits to offspring fitness by engaging in this behavior. Here, we examined the patterns of extra-pair paternity and female preferences in the yellow-rumped flycatcher (Ficedula zanthopygia). We found that female yellow-rumped flycatchers are more likely to choose larger and relatively highly heterozygous males than their social mates as extra-pair mates, that the genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…Accordingly, the number (Oh and Badyaev 2010;Dunning et al 2023) and quality (Firth and Sheldon 2016;Beck, Farine, and Kempenaers 2021) of social associations were empirically shown to be linked to reproductive success, including extra-pair mate choice (Beck, Farine, and Kempenaers 2020). Empirical studies generally find that extra-pair partners are more likely to be close neighbours (Westneat and Sherman 1997;Schlicht, Valcu, and Kempenaers 2015;Mingju et al 2017;Beck, Farine, and Kempenaers 2020;Beck, Valcu, and Kempenaers 2020), adding weight to the role of opportunism in extra-pair copulation (as empirically demonstrated by Fossøy, Johnsen, and Lifjeld 2006;and theoretically by Brommer et al 2007;.…”
Section: Introductionmentioning
confidence: 93%
“…Accordingly, the number (Oh and Badyaev 2010;Dunning et al 2023) and quality (Firth and Sheldon 2016;Beck, Farine, and Kempenaers 2021) of social associations were empirically shown to be linked to reproductive success, including extra-pair mate choice (Beck, Farine, and Kempenaers 2020). Empirical studies generally find that extra-pair partners are more likely to be close neighbours (Westneat and Sherman 1997;Schlicht, Valcu, and Kempenaers 2015;Mingju et al 2017;Beck, Farine, and Kempenaers 2020;Beck, Valcu, and Kempenaers 2020), adding weight to the role of opportunism in extra-pair copulation (as empirically demonstrated by Fossøy, Johnsen, and Lifjeld 2006;and theoretically by Brommer et al 2007;.…”
Section: Introductionmentioning
confidence: 93%
“…The travel distances required to find potential extra-pair partners can be extensive [57,58] but the energetic expenditure is expected to be low [41]. Indeed, extra-pair partners are often neighbours [24,[59][60][61]. Experimental evidence suggests that search cost may affect the distribution, but not the level, of EPP.…”
Section: ) Costs Of Acquiring Extra-pair Matesmentioning
confidence: 99%
“…Accordingly, the number (Oh and Badyaev 2010, Dunning et al 2023a) and quality (Firth and Sheldon 2016, Beck et al 2021) of social associations were shown to be linked to reproductive success, including extra‐pair mate choice (Beck et al 2020a). Extra‐pair partners are more likely to be close neighbours, and extra‐pair paternity increases as a function of population density (Westneat and Sherman 1997, Schlicht et al 2015, Mingju et al 2017, Mennerat et al 2018, Beck et al 2020a, b2020b), adding weight to the role of opportunity in extra‐pair copulation (as empirically demonstrated by Fossøy et al 2006, and theoretically by Brommer et al 2007, 2010).…”
Section: Introductionmentioning
confidence: 96%